The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1068/a41135
|View full text |Cite
|
Sign up to set email alerts
|

Holding Property in Trust: Kinship, Law, and Property Enactment on Norwegian Smallholdings

Abstract: In this paper we discuss relations between kinship, law, and property enactment. A recent revision of The Norwegian Act Relating to Concession in the Acquisition of Real Property is designed to influence the relation between subjects (property owners) and objects (properties) through ceasing the obligation of residency and cultivation on certain properties, which in turn is intended to increase sales prices of the respective properties. Drawing upon empirical research conducted in four Norwegian local authorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…People's attitudes towards property transfer, however, may differ significantly from what is stated and taken-for-granted in legal arrangements. Despite the rise in sales prices, it appears that relatively few owners are willing to sell their properties, and many of those who do sell, do so very hesitantly (Maeland 2005;Blekesaune et al 2007;Flemsaeter & Setten 2009). The present article argues that one of the main reasons for this behaviour is property owners' strong sense of home and belonging.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…People's attitudes towards property transfer, however, may differ significantly from what is stated and taken-for-granted in legal arrangements. Despite the rise in sales prices, it appears that relatively few owners are willing to sell their properties, and many of those who do sell, do so very hesitantly (Maeland 2005;Blekesaune et al 2007;Flemsaeter & Setten 2009). The present article argues that one of the main reasons for this behaviour is property owners' strong sense of home and belonging.…”
Section: Introductionmentioning
confidence: 97%
“…The second reason why an elaboration on the relationships between home and property enactment is important is that one of the main contentions held by legal geographers is that reality is more complicated and many-faceted than the hegemonic ownership model suggests (Blomley 2004;Brown 2007;Flemsaeter & Setten 2009). This model (see Singer 2000) assumes a single owner identifiable by formal rather than informal or moral claims, and that this owner enjoys all rights to use the property and to make profit from it.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, studies show that non-economic motivation may be a much more important reason for not selling small farms, and hence for absenteeism and neglect. Personal attachment, family history, kinship, sibling ownership, or 'keeping the name on the land' (Norwegian family names are often farm and place names e Karlsen, 2006;Flemsaeter, 2009;Flemsaeter and Setten, 2009) may be far more important than purely economic motivations. Clearly the sense of an obligation both to past and future generations still appears to be an important part of farmers' identity (Rønningen et al, 2005;Daugstad et al, 2006), for good or ill.…”
Section: Agricultural or Rural Policy E Or Mountain Policy? The Mountmentioning
confidence: 99%
“…In Norway, studies found a feeling of duty towards previous and future generations, the notion of being stewards not owners of the land and farm, and name and blood ties (eg. Daugstad, 1999;Daugstad et al, 2006;Flemsaeter and Setten, 2009). Pluriactivity has meant that various types of income have enabled staying on the farm.…”
Section: The Survival Of Small and Family Farmsmentioning
confidence: 99%